2019
DOI: 10.1177/0196859919865254
|View full text |Cite
|
Sign up to set email alerts
|

#MeToo Goes Global: Media Framing of Silence Breakers in Four National Settings

Abstract: This article reports the results of a qualitative media framing analysis of news coverage about #MeToo in four national contexts: the United States, Japan, Australia, and India. Comparing media coverage of a woman who became associated with #MeToo in each country reveals four media frames: brave silence breaker, stoic victim of an unjust system, recovered or reluctant hero, and hysterical slut. By identifying these frames, and their cultural variations, we add to understanding of #MeToo as an international soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The ways in which accusers’ narratives are framed may also affect the way that the public reacts to the movement and how women frame their own experiences with sexual harassment across nations. For example, Starkey, Koerber, Sternadori, & Pitchford (2019) found that across the United States, Japan, Australia, and India, women who shared their experiences with sexual harassment and assault as part of the #MeToo movement were framed as brave silence breakers, victims of an unjust system, recovered or reluctant heroes, or hysterical sluts. Cross‐national differences in these framings were used to explain differences in the ways that individuals in different nations engaged with #MeToo and the women who were viewed as emblematic of the movement.…”
Section: Discrimination Sexual Harassment and Women's Efforts To Efmentioning
confidence: 99%
“…The ways in which accusers’ narratives are framed may also affect the way that the public reacts to the movement and how women frame their own experiences with sexual harassment across nations. For example, Starkey, Koerber, Sternadori, & Pitchford (2019) found that across the United States, Japan, Australia, and India, women who shared their experiences with sexual harassment and assault as part of the #MeToo movement were framed as brave silence breakers, victims of an unjust system, recovered or reluctant heroes, or hysterical sluts. Cross‐national differences in these framings were used to explain differences in the ways that individuals in different nations engaged with #MeToo and the women who were viewed as emblematic of the movement.…”
Section: Discrimination Sexual Harassment and Women's Efforts To Efmentioning
confidence: 99%
“…In addition to that, research on the #MeToo movement across cultural contexts is limited and mostly comes from Western countries (Starkey et al 2019). Up to date, there is no research regarding the portrayal of the #MeToo movement in Croatian media done from the perspective of female public relations professionals, hence this study can serve as a starting point for further research.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, the #MeToo Movement was founded by the survivor and activist Tarana Burke. She wanted to raise awareness of women who had been abused (Starkey et al 2019). In 2017, the #MeToo hashtag went viral and woke up the world to the magnitude of the problem of sexual violence.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, though the Women's Marches, pussyhats, the #MeToo movement, as well as increasing attention on body positivity and fat shaming, it seems that feminism, once again, has a strong position in societal debates. Traditional and social media, in US contexts as well as other national contexts, extensively featured content related to these issues (Starkey, Koerber, Sternadori, & Pitchford, 2019), but as some readers remarked even girl magazines such as Teen Vogue have started to include more political and (feminist) activist content in their magazines (Banet-Weiser, 2018). Girl magazines, in part fueled by economic motivations, have started to feature political and feminist content like never before (Banet-Weiser, 2018).…”
Section: Introductionmentioning
confidence: 99%